Enhanced protein–protein interaction network construction promoted by in vivo cross-linking with acid-cleavable click-chemistry enrichment - Zhao, Lili; Zhong, Bowen; An, Yuxin; Zhang, Weijie; Gao, Hang; Zhang, Xiaodan; Liang, Zhen; Zhang, Yukui; Zhao, Qun; Zhang, Lihua (Frontiers in Chemistry, 2022)
Chemical cross-linking coupled with mass spectrometry has emerged as a powerful strategy which enables global profiling of protein interactome with direct interaction interfaces in complex biological systems. The alkyne-tagged enrichable cross-linkers are preferred to improve the coverage of low-abundance cross-linked peptides, combined with click chemistry for biotin conjugation to allow the cross-linked peptides enrichment. However, a systematic evaluation on the efficiency of click approaches (protein-based or peptide-based) and diverse cleavable click chemistry ligands (acid, reduction, photo) for cross-linked peptides enrichment and release is lacking. Herein, together with in vivo chemical cross-linking by alkyne-tagged cross-linker, we explored the click chemistry-based enrichment approaches on protein and peptide level with three cleavable click chemistry ligands, respectively. By comparison, the approach of protein-based click chemistry conjugation with acid-cleavable tag was demonstrated to permit the most cross-linked peptides identification. The advancement of this strategy enhanced the proteome-wide cross-linking analysis, constructing a 5,518 protein-protein interactions network among 1,871 proteins with wide abundance distribution in cell. Therefore, all these results demonstrated a guideline value of our work for efficient cross-linked peptides enrichment, thus facilitated the in-depth profiling of protein interactome for functional analysis.